Perancangan Ulang Interior Sekolah Dasar Islam Terpadu Az-zahra Kota Depok Dengan Pendekatan Fleksibilitas Ruang - Syaldian, Denny; Cardiah, Tita; Hambali Wilman Abdulhadi, Reza (eProceedings of Art & Design, 2024)
This research focuses on the interior redesign of SDIT Az-Zahra to create an optimal learning environment for students aged 6-12 years. As an Islamic primary school, SDIT Az-Zahra integrates the national curriculum with Islamic education, requiring an interior design that supports both academic activities and religious practices. However, the current issues at SDIT Az-Zahra, such as inefficient furniture placement, poor space organization, and the selection of furniture that does not meet students' ergonomic needs, have resulted in a less conducive learning atmosphere. A flexible space approach is proposed as a solution to address these challenges, enabling more adaptive and functional space arrangements. The redesigned interior, with a focus on flexibility and ergonomics, is expected to enhance comfort, improve the effectiveness of the teaching and learning process, and support the overall physical and cognitive development of the students. This study also highlights the importance of aligning interior design with the curriculum to create a more holistic educational environment that aligns with Islamic values. Keywords: Flexibility, Effective, School, Facilities, Learning, Adjusting